Ethical Environment in the Online Communities by Information Credibility: A Social Media Perspective - Hajli, Nick (Journal of business ethics, 2018)
With the increasing popularity of social media, a new ethics debate has arisen over marketing and technology in the current digital era. People are using online communities but they have concern about information credibility through word of mouth in these platforms. Social media is becoming increasingly influential in shaping individuals’ decision-making as more and better quality information about products is made available. In this research, a social word-of-mouth model proposes using a survey to test the model in a popular travel community. The model highlights the role of social media and social support in social networking sites (SNSs), identifying increasing credibility and information usefulness resulting in an ethical environment to adopt word of mouth. The theoretical and practical implications of the study are both detailed.